The influence of motivational factors on the frequency of participation in citizen science activities - Tiago, Patrícia (2017)
Citizen science has become a mainstream approach to collect information and data on many different scientific subjects. In this study, we assess the effectiveness of engagement and meaningful experience of participants in citizen science projects. We use motivational measures calculated from a web survey where respondents answered questions regarding to their motivation to participate in BioDiversity4All, a Portuguese citizen science project. We adapted the intrinsic motivation inventory (IMI) and considered seven categories of measurement: Interest/Enjoyment, Perceived Competence, Effort/Importance, Perceived Choice, Value/Usefulness, Project Relatedness, and Group Relatedness each of them with statements rated on a seven-point Likert scale. We received 149 survey responses, corresponding to 10.3 % of BioDiversity- 4All Newsletter’s receivers. We analyzed for possible differences among the categories pertaining to gender, age, level of education and level of participation in the project. Finally, we assessed the different patterns of motivation existing among the users. No statistical differences were found between genders, age classes and levels of education for the averages in any category of analysis. However, IMI categories presented different results for respondents with different levels of participation. The highest value of Interest/Enjoyment and Perceived Competence was obtained by the group of respondents that participate a lot and the lowest by the ones that never participated. Project Relatedness had the highest value for all groups except for the group that never participated. This group had completely different motivations from the other groups, showing the lowest levels in categories such as Perceived Competence, Value/Usefulness, Project Relatedness and Group Relatedness. In conclusion, the results from our work show that working deeply on people’s involvement is fundamental to increase and maintain their participation on citizen science projects. If, for initial recruitment and in countries with low participation culture, mechanisms of external motivation may be necessary, to guarantee higher levels of long term participation, citizen science projects should foster intrinsic motivations which can be done by incorporating in project design experiences of relatedness, capacity building, positive feedback and adapted participation modes.